ADVANCING EDUCATION QUALITY THROUGH PROGRESSIVE MADRASAH-BASED MANAGEMENT PRACTICES - Muhammad, Ratna; Malli, Rusli; Asykur, Muammar (Universitas Nurul Jadid, 2024)
This study aims to analyze and identify the management of Islamic boarding schools, madrasah-based management and the quality of Islamic high school education in Islamic boarding schools. This concept is the basis that Islamic boarding schools are also required to modify the quality of quality. This study is descriptive qualitative, namely research that is intended to reveal empirical facts objectively scientifically based on logic and scientific procedures and supported by strong methodologies and theories in accordance with the scientific disciplines being studied. The results of the study indicate that madrasah-based management in improving the quality of education in Islamic boarding schools can be seen from the important role of Islamic boarding school leaders who collaborate with stakeholders, an education system that uses a curriculum model from the ministry of Religion and the curriculum of the Islamic boarding school itself and also the quality of graduates of Islamic boarding schools. This is expected to contribute to other Islamic boarding schools to build a culture of institutional quality.